Development of integrated failure mode and effect analysis (I-FMEA) for automotive industry - Abd Rahman, Mohd Soufhwee (2013)
Emerging technologies are prominent features in the present global market. A significant amount of financial resources are spent to produce new products using the latest technologies to cater for the rising number of demands from customers for new products with lower prices and higher performance. The objectives of this study are to propose a new framework which integrates Design Failure Mode and Effect Analysis (DFMEA) and Process Failure Mode and Effect Analysis (PFMEA) to enhance current Failure Mode and Effect Analysis (FMEA) activities during new product development process. Next the study proposed to provide a valued risk priority number (RPN) by correlating between selected critical dimensional in product specifications and key process factor to enhance FMEA assessment and judgments through process performance indices (Ppk) results. Case study method is utilized in which three case studies have been carried out at automobile part manufacturing companies. An Integrated FMEA namely 1-FMEA has been establised and successfully applied to the case studies. DAIREC approach is utilized in the 1-FMEA. The I-FMEA data becomes a shared documents between two parties (Design and Process). It is a proven data for the design group to communicate and hand over new model to manufacturing process group for a Mass Production(MP). Moreover, the fmdings showed that the assessment of RPN is practical and efficient whereby it is based on the actual manufacturing process capability (Ppk) results. Through the system, engineers can easily identify process deficiencies and reduce the occurrence of producing defective products. The study is beneficial for many industries as the designed . framework is structured to fulfill satisfaction of customers in terms of higher performance products. In future, I-FMEA system can be enhanced whereby improvement on productivity will be focusing on environmental issues and human resource which are not included in this study.